2005
DOI: 10.1095/biolreprod.104.037374
|View full text |Cite
|
Sign up to set email alerts
|

In Utero and Lactational Exposure to an Environmentally Relevant Organochlorine Mixture Disrupts Reproductive Development and Function in Male Rats1

Abstract: We hypothesized that in utero and lactational exposure of male rats to a mixture of more than 15 organochlorines, resembling that found in blubber from northern Quebec seals, alters reproductive development and function. Female rats were gavaged with either corn oil (controls) or the organochlorine mixture in increasing doses (low, medium, and high) for 5 wk before mating and through gestation. Developmental effects were monitored in the male offspring from Postnatal Day (PND) 2 until PND 90. The high-dose mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 67 publications
4
37
0
Order By: Relevance
“…In addition, it can be argued that the estrogenic and androgenic equivalents contributed by xenobiotics in these highly exposed populations only are a few percent of the endogenous hormone activity, even when possible higher bioavailability of the xenobiotics is taken into consideration (Toft et al 2007). However, in controlled rodent experiments, effects on reproductive function have been observed at very low exposure levels, particularly after exposure during the fetal and postnatal development periods (Anas et al 2005; Mably et al 1992)—an issue not explicitly addressed by this project. Thus, the picture with respect to mechanisms at the cellular level is far from clear, and the possibility cannot be excluded that POPs also exert toxic effects independent of hormonal actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it can be argued that the estrogenic and androgenic equivalents contributed by xenobiotics in these highly exposed populations only are a few percent of the endogenous hormone activity, even when possible higher bioavailability of the xenobiotics is taken into consideration (Toft et al 2007). However, in controlled rodent experiments, effects on reproductive function have been observed at very low exposure levels, particularly after exposure during the fetal and postnatal development periods (Anas et al 2005; Mably et al 1992)—an issue not explicitly addressed by this project. Thus, the picture with respect to mechanisms at the cellular level is far from clear, and the possibility cannot be excluded that POPs also exert toxic effects independent of hormonal actions.…”
Section: Discussionmentioning
confidence: 99%
“…There are several pieces of evidence that indicate reproductive organs are more sensitive to detrimental effects of chemicals during critical periods of fetal and postnatal development than during adult life (e.g,, Anas et al 2005). It is therefore important to acknowledge that the research reviewed in this article does not explicitly address fetal exposures.…”
Section: Discussionmentioning
confidence: 99%
“…The physiologicallyrelevant metabolized extracts used by Campagna et al in 2009 27 contained organochlorines concentrations 5,000 to 10,000-fold lower than the environmentally relevant mixture that induced marked effects on male reproductive function in vivo in studies published by Bailey in 2002 28 and Anas et al in 2005. 29 However though the study concluded that exposure to the environmentally-relevant organochlorine mixture altered normal sperm fertility parameters in vitro the concentrations used were far higher than those found in human body fluids. Furthermore a dose response variation that is crucial in determining effects of substances was found to have no significant variation in the results when the dose is varied amongst the study participants in some studies.…”
Section: Research On Ddt and Reproductive Healthmentioning
confidence: 95%
“…Although most studies have tested the effects of only 1 or 2 chemicals (Pflieger‐Bruss and Schill, 2000; Kuriyama and Chahoud, 2004), populations are simultaneously exposed to a variety of contaminants. In earlier studies, we demonstrated that in utero and lactational exposure to an environmentally relevant organochlorine mixture adversely affected male reproduction, including decreased sperm motility, in the rat and pig models even at low, environmentally pertinent concentrations (Bailey, 2002; Anas et al, 2005). We also showed that in vitro exposure of frozen‐thawed boar sperm to the original organochlorine mixture decreased sperm motility and viability in a dose‐dependent manner (Campagna et al, 2002).…”
mentioning
confidence: 93%